Webster's New World concise Spanish dictionary - Harrap (Firm) (Hoboken, NJ : Wiley, 2006)
A Spanish-English, English-Spanish dictionary that contains more than 125,000 references and 170,000 translations and includes coverage of Latin-American Spanish, idioms, Internet vocabulary, and slang.
Spine title: Concise Spanish dictionary.
Adult.
Adult
Text in English and Spanish.
Keywords: English language -- Dictionaries -- Spanish; Spanish language -- Dictionaries -- English; English language -- Dictionaries -- Spanish; Spanish language -- Dictionaries -- English